Pendidikan Karakter Anak Jaman Now dalam Perspektif Komunikasi (Studi Pada Pendidikan Keluarga di Desa Nglumpang Kecamatan Mlarak Kabupaten Ponorogo) - Niken Lestarini (Social and Political Sciences Faculty, Widya Gama Mahakam Samarinda University, 2020)
Character education in children, are now starting to been distorted , compared with character education a child at long time ago, It has been understood or there is progress of communications technology that is very fast right now , good what happened in village and in the city will have an influence to the formation of the character of a child. The establishment of the character of a child that is not good resulted in cases that do not sought by the community as:, larceny committed by children, free sex the sons of impurity hard. In education world, the family has a role to play in the formation of a large and important. the character of a child, Expected outer dhasilkan in this research can answer any problems in the formation of the character of a child education to be the stronger face a better future. Character Education “Anak Jaman Now” in Ngelumpang Village, Mlarak District, Although the current information technology has advanced rapidly, but character education in perspective communication will depart from family education, The family education is very important to be implemented for the, by granting, enough religious education instilling discipline in order for, ideals and work hard so interwoven good communication between family members, the emergence of the openness to parents, and the environment or to community figures.